Assessing the impact of a music therapy program on attention in children with autism using behavioral and neurophysiological measures - Coates, Carolyn, author; Davies, Patricia L., advisor; Merz, Emily, committee member; Stephens, Jaclyn, committee member; LaGasse, Blythe, committee member (Colorado State University. Libraries, 2021)
Children with Autism Spectrum Disorders (ASD) are known to have difficulty with auditory sensory processing. Music therapy is a common intervention approach for children with autism to address numerous behavioral and sensory challenges using auditory stimuli. Auditory processing capabilities have also been linked with attention skills and with attentional challenges often observed in children with ASD. This study seeks to understand the differences between children with ASD and their typically developing peers in auditory processing and attention. An additional study goal is to evaluate impacts of a music therapy protocol on those constructs. Baseline measurements were collected for 10 children with ASD using the Test of Everyday Attention in Children (TEA-Ch) and EEG under a sensory registration paradigm. These data were compared to those of age- and sex-matched typically developing peers (n = 10). The children with ASD participated in biweekly music therapy over 5 weeks for a total of 10 sessions and then completed the same assessments during a post-test. The sensory registration paradigm measured passive responses to four auditory tones at two different intensities (50 and 70 dB) and two different frequencies (1 and 3 kHz). The resultant event related potentials (ERPs) were averaged into a waveform for each child at each tone and amplitudes and latencies were calculated for N1, P2, N2 and P3 components. The TEA-Ch resulted in an overall attention score and a score for each of three subdomains of attention: sustained, selective and switching. Results indicated that children with ASD performed more poorly on the TEA-Ch with significantly poorer scores in overall attention, selective attention, and sustained attention. A series of independent sample t-tests on ERP components revealed few significant differences but a trend of increased latency at N1, P2, and N2 in children with ASD for each of the four tones. Children with ASD had lower amplitude of N1 components and greater amplitude P2 components compared with the typically developing children. Following the music therapy intervention, children with ASD improved significantly in selective attention and showed a trend of improvement in switching and total attention compared to pre-testing scores. The music therapy did not result in statistically significant changes in EEG results, but a trend of increased latency was noted for N1, P2, and N2. Amplitude of the P3 component decreased following the music therapy intervention in response to the high and loud tone when age was used as a covariate. Some significant associations were found between the latency of N1, P2, and N2 and sustained and selective attention in response to the 1kHz 70dB tone across all participants at baseline (TD children and children with ASD before music therapy). In conclusion, this study shows that children with ASD have different neural processing of simple auditory tones and reduced performance in multiple domains of attention. The music therapy intervention is a promising approach to improving attention skills. The intervention did not appear to alter neural processing in the expected way of children with ASD performing more like their typically developing peers. Further research at this foundational level of neural processing may help clarify the differences in processing between children with ASD and their typically developing peers and may provide a way of monitoring interventions which seek to alter neural processing to target attentional skills and behaviors.
Keywords: autism; music therapy; electroencephalography; attention